Bengali text summarization using TextRank, Fuzzy C-means and aggregated scoring techniques - Rahman, Alvee; Rafiq, Fahim Md; Saha, Ramkrishna; Rafian, Ruhit (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.